The effect of public safety center simulation toward increased self efficacy in integrated emergency service system coordination - Riza Fikriana; Al Afik (Jurnal Keperawatan, 2018)
Emergency services are very important things to be noticed. One key factor in quality of emergency services is quality of human resources. The aim of this study was to analysis the effects of Public Safety Center simulation toward increased self efficacy in Integrated Emergency Service System Coordination. Research design was quasi experimental design with pretest – posttest without control group approach. Research sample was Public Safety Center Training participants in Dinas Kesehatan Kabupaten Purworejo on 17th-18th March 2017 with 38 participants. Research instrument was used questioner. Data was analyzed by wilcoxon test with significance 5%. The result was revealed that Public Safety Center increased self efficacy in Integrated Emergency Service System Coordination with p value < 0,001. The result showed that emergency training with simulation method could increased the quality of healthcare providers in emergency services.  With the increasing human resources capacity, it is expected that service to patients will be optimized and as expected.